Charles Taylor’s Critique of the Idea of Distributive Justice in Contemporary Political Philosophy - Iqbal Hasanuddin (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2019)
Charles Taylor is a Canadian Philosopher who is very critical to the idea of distributive justice from the liberal thinkers. One of them is John Rawls, especially his thought in A Theory of Justice. Then, this paper will examine Taylor’s view on that idea. To do so, I analyze Taylor’s Philosophy and the Human Sciences. Following Aristotelian way of thinking on the importance of society to achieve the human good, Taylor criticizes some basic assumptions which support the liberal idea of justice. For him, the emergence of the idea of distributive justice is caused by the failure of the modern thinkers to understand the essence of human being and its relation to society.